Phenomenological approach to childhood cataract treatment in New Zealand using semi-structured interviews: how might we improve provision of care. Issue 1 (28th January 2019) - Hamm, Lisa M; Boluk, Karla A; Black, Joanna M; Dai, Shuan; Thompson, Benjamin
Abstract : Purpose: To understand how we might improve the provision of medical care for children with cataracts. Design: A phenomenological design was employed. Semi-structured interviews were conducted to capture rich descriptions of the phenomena. Our goal in the interview and the analysis was to understand the sources of distress associated with treatment for cataract and deprivation amblyopia which (1) could be addressed by the medical community and (2) related to treatment adherence. Setting: Interviews were conducted by a non-clinician researcher in New Zealand (NZ) in a location chosen by informants. In NZ, the red reflex screening test is performed shortly after birth, and surgery to remove paediatric cataracts is publicly funded. Participants: Families of children who had a history of cataract in Auckland, NZ were posted an invitation to participate. Twenty families were interviewed. Results: Our analysis illustrated that informants described a wide range of experiences, from declined cataract surgery to full adherence to medical advice including years of patching for more than 4 hours a day. Across these experiences, we identified three relevant themes; timing of diagnosis, communication between the parent and clinician, and parental social support networks. Conclusion: The medical community may be better placed to support families dealing with childhood cataract by improving detection of childhood cataract, building appropriate communication pathways and promoting social support, with an emphasis on empathetic, individualised care.